Implementasi Program Sekolah Ramah Anak di Sekolah Dasar Negeri Ketintang II/140, Kecamatan Gayungan, Kota Surabaya - Januar Tino Fadil; Indah Prabawati; Tjitjik Rahaju; M Noer Falaq Al Amin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Child-Friendly School program is one of the government’s efforts to create an educational environment that is safe, comfortable, inclusive, and free from violence against children. Surabaya City, as a city implementing the Child-Friendly City policy, has implemented the Child-Friendly School Program in various educational institutions, including SDN Ketintang II Surabaya. However, in its implementation, several problems are still found, such as negative verbal behavior among students, the use of harsh language, mockery, and environmental conditions around the school that do not fully support a child-friendly culture. Therefore, this study aims to describe the implementation of the Child-Friendly School Program at SDN Ketintang II Surabaya. This research used a descriptive method with a qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation. The focus of this study used the policy implementation theory of Donald Van Meter and Carl Van Horn which includes policy standards and objectives, resources, inter-organizational communication and implementation activities, characteristics of implementing institutions, implementers’ disposition, as well as social, economic, and political conditions. The results showed that the implementation of the Child-Friendly School Program at SDN Ketintang II Surabaya has been running fairly well through the establishment of the Child-Friendly School team, positive habituation activities, collaboration with various parties, and efforts to create a more child-friendly learning environment. However, the implementation has not been fully optimal due to obstacles such as negative verbal behavior among students and social environmental conditions around the school that do not fully support a child-friendly culture.